The MEDITS maturity scales as a useful tool for investigating the reproductive traits of key species in the Mediterranean Sea - Maria Cristina Follesa (Scientia Marina, 2019)
Maturity is one of the most important biological parameters used in stock assessment programmes. Indeed, the macroscopic stage of gonadal development is an essential feature in estimating the maturity ogive and spawning stock biomass. It is also useful for determining the spawning season of a species and for monitoring long-term changes in the spawning cycle as well as for many other research needs related to the biology of fish. Despite the efforts made during the last few decades to standardize maturity stage data among all the researchers, marine biologists continue without a manageable and unique maturity scale to describe the reproductive development of fish gonads. For these reasons, the objectives of this article are 1) to investigate the biological parameters of five selected key species (Mullus barbatus, Galeus melastomus, Etmopterus spinax, Aristeus antennatus, Loligo vulgaris) with different reproductive strategies following the macroscopic maturity scales based on the same univocal criteria adopted in the MEDITS programme and described in this work; and 2) to compare them among some Mediterranean geographical sub-areas (GSAs) involved in the programme. Neither spawning periods nor size at first maturity (SFM50) for the studied species showed particular differences in the investigated GSAs.